Electrochromic Displays Manufactured by a Combination of Vapor Phase Polymerization and Screen Printing. Issue 9 (20th March 2022) - Brooke, Robert; Petsagkourakis, Ioannis; Wijeratne, Kosala; Andersson Ersman, Peter
Abstract: Smart label technology such as indicators is a growing field due to society's demand for Internet of Things devices. New materials and technologies are continuously being discovered and developed in order to provide better resolution, better performance, or more environmentally friendly devices. Within this report, screen printing technology is combined with vapor phase polymerization to synthesize three conductive polymers; poly(3, 4‐ethylenedioxythiophene) (PEDOT), polypyrrole (PPy), and polythiophene (PTh). The conductive polymers are created in micrometer resolution and investigated for their electrochromic properties. PEDOT and PPy samples are combined into printed, laminated, transmissive electrochromic displays. The technology is further advanced to establish separate PEDOT, PPy, and PTh all‐printed electrochromic displays using several screen printed layers. The PEDOT displays show improved color retention as compared to displays created with commercially available PEDOT:poly(styrene sulfonate) (PSS) with comparable contrast and switching behavior. All‐printed PPy and PTh electrochromic displays with impressive electrochromic behavior are demonstrated. More complex patterns of 7‐segment displays are created, thereby highlighting flexibility and individually switched sections of the conductive polymers. This research extends the screen printing and vapor phase polymerization combination to other conductive polymers and the potential commercialization of multicolor electrochromic displays that has been otherwise dominated by monochromatic PEDOT:PSS. Abstract : Vapor phase polymerized conductive polymers deposited by screen printing are incorporated into all‐printed, flexible, patterned electrochromic displays. Both transmissive and reflective displays of polypyrrole, polythiophene, and poly(3, 4‐ethylenedioxythiophene) are created in large scale, sheet by sheet batches.